Institutional Effects on Early Palliative Care among Mexican-Heritage Elders. (17th December 2021) - Miller, Susan; Apesoa-Varano, Ester Carolina
Abstract: This paper addresses Mexican-heritage older people's experiences with early palliative care (EPC). EPC is the early provision of medical, social and spiritual reports to relieve suffering. Empirically, Mexican-heritage older people are known to have less access to EPC and, when they access it, to receive care of lower quality. However, little work has explored how Mexican-heritage older people think about and access such care. The paper addresses this gap. Methods are longitudinal: 36 Mexican-heritage people ranging in age from 55 to 90 years completed longitudinal semi-structured qualitative interviews, for a total of 69 interviews. Results explore how respondents' participation in social institutions may mediate the effects of larger social structural constraints on their health and access to care.